Soil properties and cowpea yield after six years of consecutive amendment of composted tannery sludge - Araújo, Ademir Sergio Ferreira De; Lima, Luciano Moura; Melo, Wanderley José De; Santos, Vilma Maria Dos; Araujo, Fabio Fernando De (Editora da Universidade Estadual de Maringá - EDUEM, 2016)
ABSTRACT. This study evaluated soil properties and cowpea yield after six years of consecutive amendment of composted tannery sludge. The compost was applied annually at 0, 2.5, 5, 10, and 20 Mg ha-1 and at the end of the sixth year, the chemical and physical properties of the soil were evaluated using a randomized block design. The Cr, P, K, Ca, Na and organic C contents and the pH and cation exchange capacity increased linearly after six years of compost amendment. The soil bulk density decreased linearly while the aggregate stability index increased after compost amendment. As a consequence of the changes in the chemical and physical properties of the soil, cowpea yield showed a quadratic response to the tannery rates, with an estimated maximum cowpea yield at 8.3 Mg ha-1. In conclusion, the soil chemical and physical properties improved after six years of composted tannery sludge amendment. However, the soil pH and the Cr and Na contents increased with composted tannery sludge amendment, which influenced the cowpea yield and resulted in a quadratic response to the compost.

RESUMO. Este estudo avaliou as propriedades do solo e a produtividade do feijão-caupi após seis anos de aplicações consecutivas de lodo de curtume compostado. Anualmente, o composto foi aplicado a 0, 2,5, 5, 10 e 20 Mg ha-1 e no sexto ano as propriedades químicas e físicas do solo e a produtividade do feijão-caupi foram avaliadas em experimento de blocos casualizados. Cr, P, K, C orgânico, pH, Ca, Na, e a capacidade de troca de cátions aumentaram linearmente após seis anos de aplicação do composto. A densidade do solo diminuiu linearmente enquanto a estabilidade de agregados aumentou após a aplicação do composto. Em consequência das mudanças nas propriedades químicas e físicas do solo, a produtividade do feijão-caupi apresentou resposta quadrática às doses de lodo de curtume compostado com máxima produtividade estimada encontrada na dose de 8,3 Mg ha-1. Em conclusão, as propriedades químicas e físicas do solo melhoraram após seis anos de aplicação do lodo de curtume compostado. Entretanto, o pH do solo, bem como os teores de Cr e Na aumentaram com aplicação do lodo de curtume compostado e estes parâmetros influenciaram a produtividade do feijão-caupi que apresentou resposta quadrática.
Propriedades do solo e produtividade do feijão-caupi após seis anos de aplicações consecutivas de lodo de curtume compostado
Keywords: waste management; soil fertility; soil quality; manejo de resíduos; fertilidade do solo; qualidade do solo